Auditory Hallucinations in a Deaf Patient: A Case Report - Pedersen, Natalia; Ernst Nielsen, René (Case Reports in Psychiatry, 2013)
This case report describes the progression of symptoms in a young deaf female. Her initial psychotic symptoms occur at the age of 16, but she did not come into contact with a psychiatric treatment facility before the age of 27, where she felt symptoms were distressing. The case report describes the difficulties in evaluating psychotic symptoms in a deaf patient, as well as the use of specialized scales in combination with the standard psychiatric evaluation. The current evidence, concerning the prevalence of psychotic symptoms, as well as the influence of deafness on the understanding of psychosis, is described.